Strategies in Developing Agropolitan Areas in Indonesia - Farhanah, Laelatul; Prajanti, Sucihatiningsih Dian Wisika (Universitas Muhammdaiyah Surakarta, 2015)
Agropolitan program, so far, has not been widely acknowledged by public. Various facilities have not been optimally utilized due to their functions as there are only limited parties aware upon this program. Developing agropolitan areas through superior horticultural commodities development has not increased farmersâ exchange rate. Gaps between planning and implementation in developing agropolitan areas encourage a research with the goal of strategies in developing agropolitan areas in Rojonoto of Wonosobo district. Type of this research is a quantitative description. Primary and secondary data are used. The primary data are taken from 18 key-person agropolitan stakeholders. Priorities in developing Agropolitan areas in Rojonoto of Wonosobo district may be obtained through sequences of priority by improving human resources and technologies, the provision of production inputs, infrastructures, policies, and institutions. This study suggests that local government pay more attention to develop human resources and technologies, without disregarding to the other criteria.